On the uncertainty of sea-ice isostasy. Issue 69 (2015) - Geiger, Cathleen; Wadhams, Peter; Müller, Hans-Reinhard; Richter-Menge, Jacqueline; Samluk, Jesse; Deliberty, Tracy; Corradina, Victoria
Abstract: During late winter 2007, coincident measurements of sea ice were collected using various sensors at an ice camp in the Beaufort Sea, Canadian Arctic. Analysis of the archived data provides new insight into sea-ice isostasy and its related R -factor through case studies at three scales using different combinations of snow and ice thickness components. At the smallest scale (<1 m; point scale), isostasy is not expected, so we calculate a residual and define this as Ж ('zjey') to describe vertical displacement due to deformation. From 1 to 10 m length scales, we explore traditional isostasy and identify a specific sequence of thickness calculations which minimize freeboard and elevation uncertainty. An effective solution exists when the R -factor is allowed to vary: ranging from 2 to 12, with mean of 5.17, mode of 5.88 and skewed distribution. At regional scales, underwater, airborne and spaceborne platforms are always missing thickness variables from either above or below sea level. For such situations, realistic agreement is found by applying small-scale skewed ranges for the R -factor. These findings encourage a broader isostasy solution as a function of potential energy and length scale. Overall, results add insight to data collection strategies and metadata characteristics of different thickness products.